PENTINGNYA PENGAWASAN KREDIT DALAM MENJAGA KREDIT YANG SEHAT PADA BANK KBMI III - Anggun Hikmalia Putri, (2022)
The purpose of this study was to determine the development of credit in the KBMI III bank group, to determine the development of non-performing loans (Non Performing Loans) at the KBMI III bank, and also to know the role of credit supervision in maintaining healthy credit at the KBMI III bank. This type of research was carried out using descriptive analysis in the form of collecting data obtained through field research and also literature. The object of this research is Bank KBMI III. The results of research conducted at KBMI III Commercial Banks Credit distribution and performance evaluation of bank management go hand in hand. Changes in interest rates usually also have an impact on the amount of loans granted. Then on the performance of Bank KBMI III on non-performing loans (NPL) Bank KBMI III for the period 2020-2021 in terms of credit supervision and granting credit approvals have been carried out properly and correctly, and the role of credit supervision in maintaining healthy credit at KBMI III bank has a function to prevent bad loans or non-performing loans (NPL). Keywords : Supervision, Credit, KBMI Bank, Healthy Credit